Co-Expansion of Cytokine-Induced Killer Cells and Vγ9Vδ2 T Cells for CAR T-Cell Therapy - Du, Shou-Hui; Li, Zhendong; Chen, Can; Tan, Wee-Kiat; Chi, Zhixia; Kwang, Timothy Weixin; Xu, Xue-Hu; Wang, Shu (PLOS ONE, 2016)
Gamma delta (γδ) T cells and cytokine-induced killer (CIK) cells, which are a heterogeneous population of T lymphocytes and natural killer T (NKT) cells, have been separately expanded ex vivo and shown to be capable of targeting and mediating cytotoxicity against various tumor cells in a major histocompatibility complex-unrestricted manner. However, the co-expansion and co-administration of these immune cells have not been explored. In this study we describe an efficient method to expand simultaneously both CIK and Vγ9Vδ2 T cells, termed as CIKZ cells, from human peripheral blood mononuclear cells (PBMCs) using Zometa, interferon-gamma (IFN-γ), interleukin 2 (IL-2), anti-CD3 antibody and engineered K562 feeder cells expressing CD64, CD137L and CD86. A 21-day culture of PBMCs with this method yielded nearly 20,000-fold expansion of CIKZ cells with γδ T cells making up over 20% of the expanded population. The expanded CIKZ cells exhibited antitumor cytotoxicity and could be modified to express anti-CD19 chimeric antigen receptor (CAR), anti-CEA CAR, and anti-HER2 CAR to enhance their specificity and cytotoxicity against CD19-, CEA-, or HER2-positive tumor cells. The tumor inhibitory activity of anti-CD19 CAR-modified CIKZ cells was further demonstrated in vivo in a Raji tumor mouse model. The findings herein substantiate the feasibility of co-expanding CIK and γδ cells for adoptive cellular immunotherapy applications such as CAR T-cell therapy against cancer.